ANALYSIS OF THE INFLUENCE OF ORGANIZATIONAL JUSTICE, TRANSFORMATIONAL LEADERSHIP, AND AKHLAK CORE VALUES ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT PT JASA RAHARJA (BRANCH OF NORTH SUMATRA) - Rival Irwanson Damanik; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research aimed to determine the influence of organizational justice, transformational leadership, and AKHLAK core values ​​on employee performance with motivation as an intervening variable at PT Jasa Raharja (Branch of North Sumatra). This type of research is descriptive research. The population in this study were all employees of PT Jasa Raharja (Branch of North Sumatra), totaling 104 people. The sampling technique in this research was the Probability Sampling technique. The sampling calculation used the Slovin formula, so the sample consisted of 82 respondents. The data collection techniques were observation, interviews, questionnaires, and documentation studies (library). The data analysis method uses path analysis and hypotheses. The research results show that Transformational Leadership and Moral Core Values ​​influence employee performance at PT Jasa Raharja (Branch of North Sumatra). Meanwhile, Organizational Justice does not affect Employee Performance at PT Jasa Raharja (Branch of North Sumatra). The results of testing organizational justice and moral core values ​​do not significantly affect employee performance, with motivation as an intervening variable. At the same time, transformational leadership is increased because it significantly affects performance with an explanation as an intervening variable at PT Jasa Raharja (Branch of North Sumatra).